Pengaruh Debt Maturity Terhadap Efisiensi Investasi pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia - Bayu Pratama; Sri Fitria Jayusman (Jurnal Multidisiplin Madani, 2022)
This study aims to determine the effect of debt maturity on investment efficiency in manufacturing companies listed on the Indonesia Stock Exchange. The sample in this study was 43 companies using 86 panel data consisting of 2 years of financial data from 2018 to 2019, data collection techniques used documentation and literature study. Data processing using SPSS Version 20.0 for windows. The data analysis technique used is Simple Linear Regression and hypothesis testing consisting of t test and coefficient of determination test, and to find out how much influence debt maturity has on investment efficiency in manufacturing companies listed on the Indonesia Stock Exchange using the coefficient of determination test. The results of this study indicate that the debt maturity variable affects the efficiency of investment in manufacturing companies listed on the Indonesia Stock Exchange, it can be seen from the results of t count (2.022) > t table (1.68288), with a level of influence of 0.091 or 9.1 %.